Swertiamarin attenuates carbon tetrachloride (CCl4)-induced liver injury and inflammation in rats by regulating the TLR4 signaling pathway (Brazilian Journal of Pharmaceutical Sciences, 2018)
The aim of the present study is to illustrate the effects of swertiamarin (STM), a natural iridoid from herbal medicines, on hepatic inflammation induced by carbon tetrachloride (CCl4) in rats. Male Sprague Dawley rats were exposed to CCl4 with or without STM co-administration for 8 weeks. Our results revealed that STM administration (100 and 200 mg/kg b.w.) significantly attenuated inflammation in livers of CCl4-treated rats. STM remarkably reduced the production of interleukin-1β (IL-1β), interleukin-6 (IL-6), tumor necrosis factor alpha (TNF-α), macrophage inflammatory protein-1a (MIP1α), and monocyte chemotactic protein-1 (MCP-1) in liver tissue of CCl4-treated rats. In addition, STM treatment downregulated connective tissue growth factor (CTGF) and ser307pIRS-1 expression, which was induced by CCl4 exposure. In the process of exploring the anti-inflammatory mechanisms of STM action, we demonstrated that STM significantly inhibited Toll-like receptor 4 (TLR4) and nuclear factor kappa B (NF-κB) p65 expression in the liver. In conclusion, these results suggested that the inhibition of CCl4-induced inflammation by STM was, at least in part, due to its regulation of the TLR4 /NF-κB signaling pathway.